Tracing the journey of elements from fish feed to Nile tilapia faeces to black soldier fly larvae: a comparative approach - Yakti, Wael; Shaw, Christopher; Müller, Marcus; Mewis, Inga; Kloas, Werner; Ulrichs, Christian (Frontiers in Sustainable Food Systems, 2024)
Introduction The circular bioeconomy concept revolves around biological production cycles that reintroduce products or waste from one production system to another, aiming to maximize resource utilization while minimising environmental impact. The purpose of this study was to evaluate and compare the element flow when integrating black soldier fly larvae (BSF) production with Nile tilapia production using varying experimental fish feed. Methods Tilapia (42.5 ± 11.2 g) were reared in recirculating aquaculture systems (RAS) at 25.5°C for 10 weeks and fed equal daily rations of four experimental diets containing fishmeal (FM), poultry blood meal (PBM), black soldier fly meal (BSF) and poultry by-product meal (PM) as the single main protein source, respectively. Faeces was collected daily from settling columns installed in the RAS and subsequently fed to BSF larvae. Results and discussion The fish exhibited the highest biomass gain when fed with FM (1,001 g) or PM (901 g). The growth was lowest for those fed with PBM (406 g). The fish fed with PBM also produced the highest amount of faeces (234 g). When the fish faeces were utilized as a substrate for rearing black soldier fly (BSF) larvae and although the biomass gain did not differ significantly, the feed conversion ratio (FCR) varied among larvae fed with different fish faeces, ranging from 8.36 to 25.04. Furthermore, the concentration of analysed elements (Al, B, Ca, Co, Cu, Fe, K, Mg, Mn, Mo, Na, P, S, and Zn) varied based on the type of fish faeces provided. Results illustrate that a modulation of BSFL elemental composition is possible through manipulating the feed provided to the fish and emphasize the importance of fish feed composition for fish performance as well as the compositional quality of the larvae reared on the resulting fish faeces. Hence, if BSF larvae production is to be harnessed for the recycling of aquaculture sludge, ingredient choice and subsequent elemental composition of fish feeds are pivotal to larvae composition.